Masculinidad, libertad y nación en la Inglaterra bajomedieval (Edad Media. Revista de Historia, 2020)
This article examines how being “free” interacts with different constellations of ideas, in particular those associated with being a “man” in the specific context of thirteenth and fourteenth century England. It argues that manhood carried powerful emotional, rhetorical and hence political charges which were the consequence of both the Latin inheritance and its various adaptations in the course of the Middle Ages. It considers how these charges overlapped with those associated with being free. It examines a variety of reasons why these issues became particularly important in the thirteenth and fourteenth century, before analysing them in detail in the case of a particular mid thirteenth century political crisis in which issues of manhood, freedom and nation interacted in a new way.
Keywords: Manhood; Freedom; Liberty; Virtus; Baron; Masculinity; Nobility; Nation; Emotion; Politics; Henry III; Matthew Paris